How Islamic parties organize at the local level in post-Suharto Indonesia: an empirical study of six major Islamic parties In The Tasikmalaya District, West Java Province - Sukmajati, Mada (2011)
Many studies have explored the phenomena of Islamic parties in Indonesia, the largest predominantly Muslim country in the world. However, little effort has been made to explore the organizational structures of Islamic parties in post-Suharto Indonesia. The existing studies have also paid little attention to the role of Islamic parties at the regional level in the implementation of the decentralized system in terms of the relationship between the central and regional governments. This study is an attempt to provide a more comprehensive analysis of the way the Islamic parties at the regional level in post-Suharto Indonesia organize. In doing so, the organization of the Islamic parties is examined in three different dimensions, i.e., the party organization on the ground (political linkage between the Islamic parties and their members or supporters), the party organization in central office (leadership of the Islamic parties), and the party organization in public office (the role of the Islamic parties in policy-making). As the units of analysis, this study selects six major Islamic parties, i.e., the National Mandate Party (Partai Amanat Nasional or PAN), National Awakening Party (Partai Kebangkitan Bangsa or PKB), Reform Star Party (Partai Bintang Reformasi or PBR), United Development Party (Partai Persatuan Pembangunan or PPP), Justice and Prosperity Party (Partai Keadilan Sejahtera or PKS) and Star and Crescent Party (Partai Bulan Bintang or PBB). Despite the fact that these parties experienced a significant decrease at the national level, most of them succeeded in maintaining or increasing their level of political support at the regional level. Meanwhile, this study focuses on the Tasikmalaya district as the locus of study because it has become one of the regional bases for these parties to maintain or increase their political achievement. The district also has a long historical root in the Islamic state movement in Indonesia. As a result, Muslims in the district have a strong Islamic sentiment. This study proposes two major findings. Firstly, the way the Islamic political actors organize the Islamic parties in Tasikmalaya district suggests that these parties contain some elements of the elite-based party, mass-based party, electoralist party, and cartel party models. In other words, the Islamic parties in post-Suharto Indonesia have hybrid features. Therefore, the organizational features of the Islamic parties in post-Suharto Indonesia are not completely exceptional or unique compared to the organizational features of party politics in other developing countries. Moreover, the organizational development of the contemporary Islamic parties in Indonesia takes different trajectories. In the case of the PAN and PPP, these parties are in a transitional stage from the mass-based party model to the electoralist party model. The organizational development of the PKS suggests that this party is experiencing a maturation process of the mass-based party model, while the organizational development of the PKB, PBR and PBB shows that these parties are experiencing a stagnation process in the stage of the elite-based party. Secondly, the case of the Tasikmalaya district also indicates that the Islamic political actors in Indonesia rely on rational calculations rather than ideological considerations when they manage their Islamic parties. In this sense, the PBB, PKS, PPP and PBR as the Indonesian Islamist parties have experienced a moderation process. The way these parties organize has not led to the Islamisation of the state, but it has led to the long term Islamisation of society.
Keywords: Hochschulschrift; Geschichte 1998-2010; Islam; Parteiensystem; Tasikmalaya